2007
DOI: 10.1002/app.26333
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked chitosan doped with Y2(CO3)3 and surface energy and electrorheological properties

Abstract: Novel electrorheological materials based on crosslinked chitosan doped with Y 2 (CO 3 ) 3 were synthesized with biocompatible chitosan as the substrate of the materials. The electrorheological performance, surface energy, and thermal decomposition behavior of the materials were investigated as functions of the composition change. The results show that doping Y 2 (CO 3 ) 3 can improve effectively the electrorheological performance of crosslinked chitosan with the formation of a metal-polymer complex when the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…As shown in Table , the values for the polar component of the surface free energy of the commercial chitosan and chitin samples used in this work were particularly low, thus confirming the general trend related to chitosan previously reported, albeit without comments, by other authors. These results are in complete divergence with the corresponding values obtained for the model compounds, namely, GlcN and GlcNAc (Table ), for which both polar and dispersive components of the surface energy are high and in excellent tune with those of starch and cellulose, viz., γ s p ≈ γ s d ≈ 30 mJ/m 2 . Although GlcN hydrochloride is a water-soluble substance, the deposition of a water droplet on the surface of its pellets gave enough time to register the corresponding contact angles (see Experimental Section) before any substrate dissolution by diffusion.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…As shown in Table , the values for the polar component of the surface free energy of the commercial chitosan and chitin samples used in this work were particularly low, thus confirming the general trend related to chitosan previously reported, albeit without comments, by other authors. These results are in complete divergence with the corresponding values obtained for the model compounds, namely, GlcN and GlcNAc (Table ), for which both polar and dispersive components of the surface energy are high and in excellent tune with those of starch and cellulose, viz., γ s p ≈ γ s d ≈ 30 mJ/m 2 . Although GlcN hydrochloride is a water-soluble substance, the deposition of a water droplet on the surface of its pellets gave enough time to register the corresponding contact angles (see Experimental Section) before any substrate dissolution by diffusion.…”
Section: Resultssupporting
confidence: 88%
“…The values of the latter contribution, most around 30 mJ/m 2 , were more in tune with a polysaccharide structure and in reasonable agreement among themselves, with only one much lower figure of 17 mJ/m 2 . In another study, only the total surface energy was reported with, again, an exceedingly low value of 18 mJ/m 2 . All these data were based on contact angle measurements.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Y 2 (CO 3 ) 3 addition improved effectively the ER performance of crosslinked chitosan when the addition content is suitable. 41 The pH controlled chitosan particle/fMCT (functionalized multiwall carbon nanotube) composite showed the ER behavior under applied electric fields. 42 The chitosan succinate (II) dispersed suspension showed good electro-response property (shear stress) under the external electric field.…”
Section: Er Materials Based On Chitosanmentioning
confidence: 99%
“…A number of studies devoted to the determination of the surface energy of chitin, but mostly of chitosan, reported abnormally low values with polar contributions often close to zero (Amaral et al 2006;Ma et al 2007;Rillosi and Buckton 1995;Sionkowska et al 2006;Wong et al 1992;Yamamoto et al 1999). No cross-reference was provided by these authors and, more surprisingly, no discussion followed the report of these odd results.…”
Section: Chemical Modificationsmentioning
confidence: 74%